1999
DOI: 10.1152/jn.1999.81.2.596
|View full text |Cite
|
Sign up to set email alerts
|

MST Neuronal Responses to Heading Direction During Pursuit Eye Movements

Abstract: As you move through the environment, you see a radial pattern of visual motion with a focus of expansion (FOE) that indicates your heading direction. When self-movement is combined with smooth pursuit eye movements, the turning of the eye distorts the retinal image of the FOE but somehow you still can perceive heading. We studied neurons in the medial superior temporal area (MST) of monkey visual cortex, recording responses to FOE stimuli presented during fixation and smooth pursuit eye movements. Almost all n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
1
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 41 publications
4
65
1
2
Order By: Relevance
“…This ability implies that the neural processing of optic flow must somehow take into account the rotation of the eyes. Indeed, several authors have shown that the heading tuning of some neurons in areas MST (Bradley et al, 1996;Page and Duffy, 1999;Shenoy et al, 1999Shenoy et al, , 2002Ilg et al, 2004) and VIP (Zhang et al, 2004) compensates for smooth pursuit eye movements. It has been argued that pursuit compensation is equivalent to a transformation 2 ] as a function of VVR and EPR.…”
Section: Discussionmentioning
confidence: 99%
“…This ability implies that the neural processing of optic flow must somehow take into account the rotation of the eyes. Indeed, several authors have shown that the heading tuning of some neurons in areas MST (Bradley et al, 1996;Page and Duffy, 1999;Shenoy et al, 1999Shenoy et al, , 2002Ilg et al, 2004) and VIP (Zhang et al, 2004) compensates for smooth pursuit eye movements. It has been argued that pursuit compensation is equivalent to a transformation 2 ] as a function of VVR and EPR.…”
Section: Discussionmentioning
confidence: 99%
“…The human homolog of monkey MST is also implicated in human heading detection tasks (Beardsley & Vaina, 2001). Heading appears to be represented as a population code in both primate MSTd and human MT complex (hMT+) (Beardsley & Vaina, 2001;Page & Duffy, 1999). It is the MT -ON-center OFF-surround network that enables it to respond to differential motion.…”
Section: Introductionmentioning
confidence: 99%
“…Eye movement sensitive gain fields have been shown to efficiently deal with real eye rotations in template models (Beintema & van den Berg, 1998;Elder et al, 2008). Consistent with such a mechanism, some primate MSTd cells have responses that are modified during pursuit eye movements (Page & Duffy, 1999). Although these data are consistent with a template model with gain fields, they are hard to explain using models that produce a rotation-free optic flow representation before inputting to MST, such as decomposition or differential models.…”
Section: Discussionmentioning
confidence: 99%
“…Such a distributed representation of heading has been described in primates and humans (Beardsley & Vaina, 2001;Page & Duffy, 1999). The model is computationally efficient, demonstrating that a small number of adaptive flow filters, or templates, distributed across visual space can produce high levels of accuracy with a wide range of inputs.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation